2018
DOI: 10.1259/bjr.20170798
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and imaging features of Kaposiform Hemangioendothelioma

Abstract: Five masses with DWI showed slightly restricted diffusivity. A hypervascular mass accompanied by KMP and reticular lymphedema, with speckled hypointense signal TWI signal, especially in pediatric patients, is highly suggestive of the diagnosis of KHE. Advances in knowledge: Speckled hypointense signal TWI signal, and notable enhancement were unique features of KHE. KHE showed slightly restricted diffusivity on DWI, commonly accompanied by KMP and reticular lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 22 publications
0
38
0
1
Order By: Relevance
“…Deep KHE with KMP should be considered in patients presenting with an unexplained severe thrombocytopenia and coagulopathy, especially in patients coexisting with cutaneous purpura and severe anemia. MRI scan of the abdomen and chest should be recommended for such patients [84,85].…”
Section: Diagnosismentioning
confidence: 99%
“…Deep KHE with KMP should be considered in patients presenting with an unexplained severe thrombocytopenia and coagulopathy, especially in patients coexisting with cutaneous purpura and severe anemia. MRI scan of the abdomen and chest should be recommended for such patients [84,85].…”
Section: Diagnosismentioning
confidence: 99%
“…Schmid et al insisted that meticulous surgical excision must be considered as the first line of treatment for KHE, while Ji et al proposed that sirolimus could be regarded as the first option [4,9]. KHE often manifests as an immovable enlarging mass [10]. Our patient's lesion was located deep inside, alongside the thoracic vertebral bodies.…”
Section: Discussionmentioning
confidence: 82%
“…Regarding MRI findings in TA and KHE, previous studies have reported that the imaging characteristics of TA and KHE were similar to other vasoproliferative neoplasms, although KHE tended to be larger, more ill‐defined and infiltrative . Several case reports and series have described imaging findings associated with KHE exhibiting ill‐defined margins, multiplanar involvement, diffuse enhancement, isointensity relative to muscle on T 1 ‐weighted imaging, hyperintensity on T 2 ‐weighted imaging and destruction/remodeling of adjacent bone. In our study, all lesions presented as irregular soft tissue masses in subcutaneous regions, with iso‐ or hypointensity to muscle on T 1 ‐weighted sequences and hyperintense T 2 signal.…”
Section: Discussionmentioning
confidence: 95%